Distinctive features of verbs in the German language of the Old Believers living in Masuria - Jorroch, Anna (Papers in Linguistics, 2024)
When the Old Believers fleeing persecution after the liturgical reform of Patriarch Nikon in the Russian Orthodox Church in the 17th century arrived in Masuria in 1830, the region belonged to East Prussia. Until 1945, they were exposed to German culture, into which they gradually assimilated and learned the German language. After World War II, the area was divided, with its northern part annexed by the USSR and the southern part, i.e. Masuria, incorporated into Poland. The generations of Old Believers who were born in Masuria until the mid-1950s are trilingual, speaking a Russian dialect as well as Polish and German. As part of field research conducted by the author from 2007 to 2015, interviews with 23 Masurian Old Believers speaking German were registered and analysed considering the trilingualism of the speakers (Jorroch 2015). The article presents interesting phenomena in the speech of the respondents, such as double perfect tense constructions, a characteristic construction of the conditional mode with the modal verb mögen, or an archaism in the construction of the perfective aspect of the verb.